Analisis Quality of Service (QoS) Menggunakan Standar Parameter Tiphon pada Jaringan Internet Berbasis Wi-Fi Kampus 1 Unjaya - Nisa, Isnaini Syarifatun Nisa; Rahmat Miyarno Saputro; Tegar Fatwa Nugroho; Alfirna Rizqi Lahitani (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Internet is a very important need in the life of people in the world. Universities can exchange information and share data and communicate with the internet network. General Achmad Yani University Yogyakarta (Unjaya) uses the internet network for activities that occur on campus. QoS testing or internet network performance aims to maintain the stability of network access on the Unjaya campus and reduce the risk of problems such as delays in data transmission. In addition, this research also aims to determine the results of signal quality measurements in the Unjaya real-time area. In this research, QoS measurement is done by using wireshark application. The QoS parameters measured are throughput, delay, jitter, and packet loss. Based on the measurements taken, the results obtained for QOS measurements show that WiFi network performance based on throughput, delay, jitter, and packet loss parameters is in the good category. The final result obtained after measuring QoS is that the Internet network at Campus 1 Unjaya is in the medium category based on TIPHON standardization with an index value of 3.